2019
DOI: 10.18332/tpc/109784
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use among male inmates and their attitudes toward its prevention in Khartoum State: A cross-sectional study

Abstract: INTRODUCTION Tobacco use remains the most preventable cause of death and disability, with prisoners being a neglected population of tobacco users. The aim was to determine the prevalence of tobacco use and attitudes toward its prevention among adult male prisoners. METHODS We conducted a descriptive cross-sectional study among 349 adult male inmates from three prisons in Khartoum State. The interview questionnaire included questions related to tobacco use status, type of tobacco used, previous attempts to quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
4
0
2
Order By: Relevance
“…A study investigating knowledge, attitude, and practice of Toombak among school workers in Khartoum state reported that 9.6% school workers confirmed ever use of Toombak and the daily users were 64.7% [27]. The prevalence of tobacco smoking among diabetics was found to be 33.9% [28], while the prevalence of tobacco use among male prisoners in Khartoum was found to be 100%, of whom 78% were Toombak users, 57% cigarette smokers, 30.9% used both cigarette and Toombak, 0.6% used cigarette and water pipe while 3.2% used cigarette, Toombak and shisha together, and shisha users were 3.8% [29] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study investigating knowledge, attitude, and practice of Toombak among school workers in Khartoum state reported that 9.6% school workers confirmed ever use of Toombak and the daily users were 64.7% [27]. The prevalence of tobacco smoking among diabetics was found to be 33.9% [28], while the prevalence of tobacco use among male prisoners in Khartoum was found to be 100%, of whom 78% were Toombak users, 57% cigarette smokers, 30.9% used both cigarette and Toombak, 0.6% used cigarette and water pipe while 3.2% used cigarette, Toombak and shisha together, and shisha users were 3.8% [29] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed [33] 1 1 1 1 1 −1 0 0 1 0 1 0 0 0 Idris et al [5] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Almahdi et al [13] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Mahmoud et al [11] 1 1 1 1 −1 0 0 0 1 0 1 0 0 0 Dirar [14] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Elamin et al [12] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Elmanna [18] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Osman et al [16] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Ahmed et al [17] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Almahdi et al [24] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Mohamedet al [19] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Othman et al [22] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Almahdi et al [23] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Elmosaad et al [26] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Gadalla et al [21] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 El-Amin et al [25] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Atari [20] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Awooda and Shashati [29] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Awadalla et al [28] 1 1 1 1 −1 0 0 0 1 0 1 0 0 0 Almahdi et al [27] 1 1 1 1 1 0 0 0 1 0 1 0 0 0 Key A Was the research question or objective in this paper clearly stated? B Was the study population clearly specified and defined?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos hallazgos corroboran la investigación que identificó el aumento de la frecuencia del uso de tabaco entre presos, con la justificación de conseguir lidiar con el estrés asociado al encarcelamiento (38) . El mayor consumo de SPAs por los prisioneros en Ecuador también estuvo asociado al encarcelamiento (39) , retratando la necesidad de abordar ese asunto en el ambiente carcelario para la planificación de acciones eficaces y efectivas con las PPLs.…”
Section: Discussionunclassified
“…Esses achados corroboram uma pesquisa que identificou o aumento da frequência do uso de tabaco entre presos com a justificativa de conseguirem lidar com o estresse associado ao encarceramento (38) . O maior consumo de SPAs pelos prisioneiros no Equador também esteve associado ao encarceramento (39) , retratando a necessidade de abordar esse assunto no ambiente prisional para o planejamento de ações eficazes e efetivas com as PPLs.…”
Section: Discussionunclassified